1991
DOI: 10.1073/pnas.88.24.11349
|View full text |Cite
|
Sign up to set email alerts
|

Critical cytoplasmic region of the interleukin 6 signal transducer gp130 is conserved in the cytokine receptor family.

Abstract: Interleukin 6 (IL-6) signal is transduced through gpl30 that associates with a complex of !L-6 and IL-6 receptor. Truncations or amino acid substitutions were introduced in the cytoplasmic region of human gpl30, and the mutant cDNAs were transfected into murine interleukin 3-dependent cells to determine amino acid residues critical for generating the IL-6-mediated growth signal. In the 277-amino acid cytoplasmic region-of gpl30, a 61-amino acid' region proximal to the transmembrane domain was sufficient 'for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
341
3
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(357 citation statements)
references
References 34 publications
9
341
3
3
Order By: Relevance
“…Box 1, a proline-rich region encompassing residues 245-250 in rat PRLR, is the most highly conserved feature within the cytoplasmic domain of cytokine receptors (26). Interestingly, our study did not identify Box 1 as an internalization signal.…”
Section: Residuesmentioning
confidence: 47%
See 1 more Smart Citation
“…Box 1, a proline-rich region encompassing residues 245-250 in rat PRLR, is the most highly conserved feature within the cytoplasmic domain of cytokine receptors (26). Interestingly, our study did not identify Box 1 as an internalization signal.…”
Section: Residuesmentioning
confidence: 47%
“…25). Mutational analyses of PRLR, as well as of several members of the PRL/GH/cytokine receptor superfamily, have shown that the membrane-proximal region, which includes a proline-rich motif termed Box 1 (26), is essential for signal transduction, since it mediates receptor association with Janus kinases (for review, see Refs. 25 and 27).…”
mentioning
confidence: 99%
“…SIRPα1 also contains a proline-rich motif that conforms to the proline-rich box 1 region of cytokine receptors. The proline-rich region in the cytokine receptors mediates the association between the JAK kinases and the cytokine receptors (23,24,28). Deletion of the proline-rich region of SIRPα1 or proline to alanine mutation of conserved prolines in this region had no effect upon the association of JAK2 with SIRPα1.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of transfected BAF ± B03 pro-B cells needed the contribution of both signals derived from gp130: STATs induced anti-apoptotic factors, whereas MAP kinase activation was necessary for proliferation . Short-term DNA synthesis in these cells, however, had even been observed with a truncated gp130 lacking all tyrosine residues required for SHP-2 and STAT activation (Murakami et al, 1991).…”
Section: Introductionmentioning
confidence: 94%